Manajemen Perpajakan: Analisis Perencanaan Pajak Pertambahan Nilai di Indonesia (Kajian Literatur) - Nariswari, Anindya; Ardelia, Sarah Selli; Wahono, Puji; Pahala, Indra (Jurnal EMT KITA, 2024)
Tax planning for Value Added Tax (VAT) in Indonesia is an important important aspect in managing company tax obligations efficiently. This study examines various VAT tax planning strategies, including the crediting of input tax, evaluation of VAT compensation, delaying the issuance of tax invoices, purchases from PKP sellers, and technical implementation. Through the application of these strategies, companies can reduce tax burdens legally, increase operational efficiency, and increase profitability. Research not only highlights the importance of tax planning in reducing tax obligations, but also provides practical guidelines to assist companies in managing their tax obligations more efficiently and effectively. In addition, research also shows how companies can use various tax incentives provided by the government to achieve these goals. The results of the study are known that strategic tax planning for VAT in Indonesia involves the use of tax incentives, ensuring the structure of transactions is optimized, and comply with relevant government laws and government policies related to VAT. Through effective VAT tax planning, companies can streamline their tax management, reduce tax burdens legally, and ultimately increase efficiency and profitability.